2006
DOI: 10.1021/es061470h
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Group Elements in Airborne Particles in Mexico City

Abstract: Automobile exhaust catalysts using platinum group elements (PGE) have been mandatory on new cars in the Mexico City Metropolitan Area (MCMA) since 1991. Platinum, Pd, Rh, Ir, and Os concentrations and the isotopic composition of Os were determined in PM10 samples from the MCMA. Samples were prepared by isotope dilution NiS fire assay, and analysis was performed by magnetic sector ICP-MS using a single collector instrument for Pt, Pd, Rh, and Ir analysis and a multicollector instrument for Os analysis. Pt, Pd, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 28 publications
4
53
0
Order By: Relevance
“…However, the PGE behavior in tree sequences has not been published, in spite that in the last decade, the impact of these elements in urban areas has been demonstrated from different environmental samples (soils, dust, particulate matter, biological tissues). Previously reported data of PGE (Rauch et al 2006;Morton-Bermea et al 2014, 2015. The PGE concentration trends in tree-ring sequences from Chapultepec Park (trees A, B and C) appear to be in accordance with this enrichment, showing a sharp increase after the early 1990s, which is not observed in the tree-ring sequences from tree D (Amealco), growing in a remote area.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…However, the PGE behavior in tree sequences has not been published, in spite that in the last decade, the impact of these elements in urban areas has been demonstrated from different environmental samples (soils, dust, particulate matter, biological tissues). Previously reported data of PGE (Rauch et al 2006;Morton-Bermea et al 2014, 2015. The PGE concentration trends in tree-ring sequences from Chapultepec Park (trees A, B and C) appear to be in accordance with this enrichment, showing a sharp increase after the early 1990s, which is not observed in the tree-ring sequences from tree D (Amealco), growing in a remote area.…”
Section: Resultssupporting
confidence: 69%
“…Morton et al (2001) report PGE concentration in urban topsoils. Afterward, Rauch et al 2006 reported data related to de Pt, Pd and Rh concentration in PM 10 collected in representative sites in Mexico City. Morton-Bermea et al 2014 present a spatial and temporal distribution of Pt in PM 2.5 collected in Mexico City.…”
Section: Introductionmentioning
confidence: 99%
“…A small anthropogenic input of Os that is originally derived from mantle may reduce the 187 Os/ 188 Os ratios. Elevated Os concentrations have been found in environmental samples and are thought to be the result of emission from automobile catalysts in which Os occurs as an impurity (Fritsche and Meisel 2004;Poirier and Gariepy 2005;Rauch et al 2005Rauch et al , 2006. In this study, almost all samples have higher Os contents and lower 187 Os/ 188 Os ratios than the background values ( Fig.…”
Section: Osmiummentioning
confidence: 52%
“…Until present, other than Pt, Pd and Rh, only limited studies have been reported for automobile catalyst-related Ru and Ir in environmental samples (Muller and Heumann 2000;Ely et al 2001;Fritsche and Meisel 2004;Rauch et al 2004aRauch et al , b, 2006. Iridium has been used in some new diesel catalysts together with Pt (Palacios et al 2000).…”
Section: Ruthenium and Iridiummentioning
confidence: 99%
“…17 A recent study on sediments from Massachusetts Bay, Cape Cod Bay, and Boston Harbor (all USA) reported background Os concentrations in the range of 22 Os ratios identify an anthropogenic input and thus can be used to trace the PGE source(s). 12,16,[19][20][21][22] The monitoring of Re will be especially important since to date virtually nothing is known about its behavior in the environment and its risk for humans.…”
mentioning
confidence: 99%